Alpha and beta diversity of lepidoptera in eucalyptus plantations in the Amazonian region of Brazil - Zanuncio, José Cola; Lemes, Pedro Guilherme; Santos, Germi Porto; Wilcken, Carlos Frederico [UNESP]; Zaché, Bruno [UNESP]; Pinto, Rosenilson; Serrão, José Eduardo (My University, 2014)
The Lepidoptera are among the insect groups with the greatest species diversity and ecological services. The distribution, abundance and variation in time and space of species in natural communities are important. The occurrence of pests (primary pest species) and those species with potential to cause damage (secondary pest species), plus other species, are studied in monitoring programs in forest plantations as groups I, II and III, respectively. The objective of this work was to study alpha and beta diversity patterns, and the effect of native forest in these indexes by monitoring Lepidoptera in eucalyptus plantations in the Amazonian region of Brazil. Surveys were conducted with light traps at 4 sites in this region. Alpha diversity was calculated with the Jackknife first-order procedure and beta diversity with the Jaccard index in order to estimate the dissimilarity per point and the effect of the distance between the native forest and the plantations on the Lepidoptera fauna. The richness showed 10 or 11 species of group I; 9 or 10 species of II and 378 to 409 species of III, without differences per group between regions. The curves of accumulated number of primary pest species stabilized between the 15th and 35th samplings and those for secondary pest species stabilized in the range from 20th to 70th samplings, with variations among sites. The estimation of richness for species of group III ranged from 50 to 100 species with a steep slope of the curve until approximately the 60th sampling with a slow increase and a tendency of stabilization in the 4 areas after this date. The primary pest species were the same in all areas and therefore their beta diversity was zero. The dissimilarity of secondary pests was similar between areas except for Felipe. Group III showed lower dissimilarity between Caracuru and Ponte Maria (14.88%) and highest values between Felipe and Pacanari (21.64%). The lower number of individuals of group I in Felipe and Ponte Maria and lower species richness of group III in Felipe can be explained by the proximity of eucalyptus plantations to the native forest. The knowledge of population dynamics and species richness of Lepidoptera defoliators is important for pest management. These indexes allow a better detection of species with a history of damage and decision-making with the most appropriate preventive measures for each situation.
Keywords: Defoliator; Forest entomology; IPM; Primary pests